Transcatheter therapy for Lutembacher's syndrome: The road less travelled - Ramalingam Vadivelu; Saujatya Chakraborty; Shiv Bagga (Wolters Kluwer Medknow Publications, 2014)
An 18-year-old male with Lutembacher's syndrome underwent balloon mitral valvotomy (BMV) and device closure of the atrial septal defect (ASD). BMV necessitated technical modification of taking the Inoue balloon over the wire (OTW) into the left ventricle (LV). The procedure was complicated by slippage of ASD device into the right atrium, which was managed successfully by percutaneous retrieval, and deployment of a larger device. The case highlights the challenges associated with the seemingly easy transcatheter therapy for this disease entity.